Adaptive handover control in IP-based mobility networks - Taeyeon Park; Arek Dadej (Journal of Telecommunications and Information Technology, 2003)
In this paper, we propose framework for an adaptive handover control architecture (AHCA), which aims at enhancing overall IP handover performance while maximising utilisation of resources in wireless access networks. The IP handover procedures in the AHCA adapt dynamically to network conditions, as well as to a wide range of user profiles and application quality of service (QoS) requirements. To confirm our expectations that the AHCA will bring performance benefits in heterogeneous mobile IP networking environment, we have investigated basic performance characteristics of different handover mechanisms. The preliminary simulation results demonstrate that the AHCA will bring significant performance improvements as compared with non adaptive IP handovers.